Collecting in Sicily in the Nineteenth Century: Baron Judica and the Wonders of Ancient Akrai .......... 129 - Santagati, Elena (Collecting Antiquities from the Middle Ages to the End of the Nineteenth Century: Proceedings of the International Conference Held on March 25-26, 2021 at the Wrocław University Institute of Art History, 2021)
The first studies on the ancient Syracuse settlement in Acrae (663 BC Thuc. 6,5) date back to the 16th century, when Fazellus located the ancient Greek apoikia just west of modern-day Palazzolo Acreide (Syracuse). However, the actual archeological field study in the ancient Greek polis took place as late as 1809, thanks to Baron Judica’s passion towards archeology. He devoted his life and all his wealth to ancient Acrae, where he brought to light its vestiges, thereby giving back to Sicily a piece of its ancient history. Thanks to his tireless effort, passion, and dedication, the Judica collection boasted over 3,000 artifacts, including 892 exquisite Greek vases. This paper will focus on how this very collection was formed.